A responsabilidade humana: ética e filosofia da religião em Emmanuel Lévinas - Marra, Suzie (2010)
This dissertations aims at showing a new aspect of ethics: the ethical responsibility as a primordial and essential structure of the human being. This is the ethical perspective proposed by Emmanuel Lévinas. Its fundamental aspects will thus be here presented as constituent elements of the human responsibility that charges the person as a task or an individual and inalienable mission, integrating the should be of the person. In order to have a better understanding and clearance on this new ethical perspective that embodies human responsibility on a structural level, one proposes firstly to locate the conjuncture (particular and historical) in which one can place the author s thoughts; secondly to put the basic matrices of the Judaic thought as possible influences in the Levinasian thinking; and lastly, to demonstrate the religious philosophical basis that found the author s ethical thought, according to himself